P2_6 A Solar Diet Plan - Staab, Daniel; Watkinson, Emily Jane; Rogerson, Zach; Walach, Maria-Theresia (Physics Special Topics, 2012)
The solar mass loss per year from fusion and solar wind outflow was estimated, and found to be 1.836x1017 kg. Calculations showed that the contribution from fusion amount to approximately three times that of the solar wind. The effect on Earth was determined to be an increase in orbital radius of 1.38 cm per year.